109k views
3 votes
In order to solve for the variable in the equation 2 (4 x + 3) + 4 = 3 x minus (2 x + 4), Giovanni first applies the distributive property. Which equation is a result of this step?

User Geovanni
by
4.8k points

2 Answers

4 votes

Answer:

B. 8x+6+4=3x-2x-4

Explanation:

If you need it solved the work is in the image below!

In order to solve for the variable in the equation 2 (4 x + 3) + 4 = 3 x minus (2 x-example-1
User Vjalle
by
5.7k points
0 votes

Answer:

8x+6+4=3x-2x-4

Explanation:

the distributive property is multiplying the numbers outside of the parentheses into the inside

2×4x=8x

2×3=6

8x+6+4

Then do the same thing on the other side

Which gets you

3x-2x-4

so he has the equation

8x+6+4=3x-2x-4

User Cameronjonesweb
by
4.8k points